An Innovative Roadmap to Value Co-Creation in Agriculture - N. V. Cherner (Vestnik MGIMO-Universiteta)
Book review: Campos H. (ed.). 2021. The Innovation Revolution in Agriculture: A Roadmap to Value Creation. Springer Nature Switzerland AG. DOI https://doi.org/10.1007/978-3-030- 50991-0